Postoperative graft thrombosis in Fontan procedure - Sarıgül, Ali; Farsak, Bora; Koramaz, İsmail and Tok, Mustafa and Yurdakul, Yurdakul (The Turkish Journal of Pediatrics, 2000)
Fontan repair could be used as the definitive palliation in many forms of complex cyanotic congenital heart disease. But thrombosis can occur after a modified Fontan operation (right atrium-right ventricular connection with a conduit). Appropriate management of this complication includes thrombolytic therapy, thrombectomy and revision (if surgically remediable causes of the thrombosis are identified) or redo operation. Two repair operations were performed for the treatment of thrombosis of the right side of the heart in patients in whom we had previously performed Bjork modification (right atrium-right ventricular connection with a conduit). The thromboses occurred 6 and 9 years after the operation, respectively. In both cases, the redo Fontan operation was successfully performed using a dacron tube graft. Patients were anticoagulated after the operation. Risk of thrombosis of the right side of the heart after the Fontan repair may be minimized with the use of prophylactic anticoagulation in high-risk patients soon after the operation.